Oceans : Documents of Contemporary Art - Syperek, Pandora; Wade, Sarah (London : Whitechapel Gallery, 2023)
Artist surveyed include : Ader, Bas Jan ; Agar, Eileen ; Akomfrah, John ; Amin, Heba Y. ; Ashoona, Shuvinai ; Beaumont, Betty ; Bucher, Heidi ; Coates, Marcus ; Diawara, Manthia ; Dobrowolski, Chris ; Eshraghi, Lùeuli et al.
Oceans cover 70 percent of the Earth’s surface, dividing and connecting humans, who carry saltwater in their blood, sweat and tears. They represent a powerful nonhuman force, rising, flooding, heating and raging in unprecedented ways as the climate crisis unfolds. Artists have envisioned the sea as a sublime wilderness, home to mythical creatures and bizarre species, a site of new beginnings and tragic endings, both wonderous and disastrous.(from publisher)
boek